Revision Surgery of Osteolysis of Carpal Bones Caused by Osteomyelitis after Pancarpal Arthrodesis with an En bloc Corticocancellous Bone Autograft - Senn, Markus; Kircher, Patrick R.; Unger, Martin (VCOT Open, 2025)
Various complications have been reported after pancarpal arthrodesis, but to our knowledge, no reports of complete carpal bone osteolysis leading to failure of the pancarpal arthrodesis have been described. Possible causes in our cases include primary or surgical trauma, as well as bone infections. The revision surgery in our cases employed a corticocancellous bone autograft from the iliac wing, which has been successfully used in nonunion fractures to refill bone defects. In both cases the graft was accepted well, complete bone fragment ingrowth and remodelling, and a stable arthrodesis of the carpal joint was achieved. In subsequent rechecks, the animals displayed good weight-bearing on the afflicted limbs.
Keywords: surgical-site infection; revision surgery; bone defect healing